The New Ecuadorian Public Management and the Optimization of Resources through Public Procurement - Logroño-Santillán, Marco Antonio (2022)
The administrative models of public management, based on the historical context in which they have been implemented, largely establish the different relationships between the State, Public Administration and society; which constitutes a complex phenomenon to investigate. For this reason, the objective of this work is to analyze the new public management for the optimization of resources through public contracting, which will be contrasted after a specific documentary review, in such a way that similarities and differences between said models can be established, which constitute the object of study. The research seeks to identify variables that help identify the problems of public management in Ecuador, through the compilation of the SAP Business Explorer platform, which allows exploring corporate information quickly and directly; and, later, a case is shown to publicize the application of what is described in the methodology. Finally, it is important to analyze public contracting, which allows the optimization of resources, thus leaving latent academic discussion about what would be the long-awaited ideal model, which above all else allows reducing the asymmetry of social classes.